تحليل – الكلفة – الحجم – الربح – في ظل نظام الكلفة على أساس الأنشطة - التكريتي اسماعيل يحيى; عبد الغني فريال كاظم (Journal of Economics and Administrative Sciences, 2008)
Recent advancement in production technologist of manufacturing processes have left an important effects upon cost structure. Moreover the problem for providing necessary and adequate information for managerial decision making. Therefore the cost – volume – profit analysis under the new activity based costing has replace the old method for Analysing the relation between C.V.P with respect to profit planning and control. In brief the C.V.P object is to discuss the effect of changes on profit resulting from changes in sales volume, cost of manufacturing and selling price. This study consists of four chapters: The first chapter dealt with method of analysing costs – volume and profit according to the traditional approach. The second chapter dealt with the C.V.P analysis under the new approach activity based costing. The third chapter dealt with studying the company research sample and the practical application of the C.V.P analysis under the traditional and the new approach, using the actual information from the books and other sources of data obtained from the Electrical industries company. Finally, the forth chapter summarized the major conclusions and presented some recommendations that related to the research area.